MCCAW, Dick. Bakhtin and Theatre: Dialogues with Stanislavsky, Meyerhold and Grotowski [Bakhtin e o teatro: diálogos com Stanislavsky, Meyerhold and Grotowski]. Abingdon: Routledge, 2015. 264p. - Gonçalves, Jean Carlos; Santos, Marcelo Cabarrão (Bakhtiniana. Revista de Estudos do Discurso, 2016)
Resenha.